NATURAL AND MAN-INDUCED STRESS EVOLUTION OF SLOPES: THE MONTE MARIO HILL IN ROME - Bozzano F.; Martino S.; Priori M. (My University, 2006)
The paper deals with stress-release effects induced by man-made cuts or excavations into natural stiff clay slopes that experienced erosion in response to valley deepening. The study was focused on the Monte Mario hill in Rome (Italy), which formed part of an area of recent urban expansion. The methodology of the study relied on a reference engineering-geology model, which was developed on the basis of site and laboratory data and stress–strain analyses. The latter analyses were carried out with the finite-difference code FLAC 4.0. Numerical modelling was based on a sequential approach, taking into account the main evolutionary stages of the Tiber river valley in Romeȁ9s urban area and then making cuts at the bottom of the slope located south of the Monte Mario Astronomical Observatory. The simulation revealed the stress-release effects that fluvial erosion and excavation fronts have caused on the investigated slopes and their consequent gravitational instabilities. These processes appear with metre-scale displacements, followed by stress-release cracks (actually observed on the slopes under review). In quantifying stress-release deformations, the simulation took into account the possible role of creep in the observed retardation of stress-release effects.
Keywords: STIFF CLAYS; STRESS-RELEASE; MAN-MADE CUTS; SLOPE STABILITY; NUMERICAL MODELS